2004
DOI: 10.1037/1064-1297.12.2.91
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Instructions and Nicotine Dose on the Subjective and Reinforcing Effects of Smoking.

Abstract: Subjective and reinforcing effects of smoking a cigarette were examined within a 2 x 2 modified balanced-placebo design, which manipulated instructions about nicotine content (i.e., told regular nicotine vs. told low nicotine) and actual nicotine dose (given a regular nicotine brand vs. a denicotinized brand). Most ratings of the nicotine content and reward value of cigarettes were higher for those told regular nicotine versus told low nicotine, and for those given regular nicotine versus given low nicotine. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
51
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 27 publications
8
51
0
1
Order By: Relevance
“…Consistent with past research, we expected to find a significant effect of instructional set on ratings of craving/urge reduction (Juliano & Brandon, 2002) and cigarette satisfaction (Perkins et al 2004), as well as other dimensions of the CES. We sought to expand on these findings by assessing smoking urges, tension, and energy at three different points in the experiment.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Consistent with past research, we expected to find a significant effect of instructional set on ratings of craving/urge reduction (Juliano & Brandon, 2002) and cigarette satisfaction (Perkins et al 2004), as well as other dimensions of the CES. We sought to expand on these findings by assessing smoking urges, tension, and energy at three different points in the experiment.…”
supporting
confidence: 84%
“…Juliano and Brandon (2002) used a 3-hour abstinence interval and found that both instructional set and nicotine reduced the urge to smoking. In contrast, Perkins et al (2004) found no reduction in cravings using minimallyabstinent smokers. We asked our participants to abstain for 8 hours and found an effect of nicotine on the "craving" item of the CES as well as an effect of instructional set over time using the QSU.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Ces stimulis peuvent être à proximité (l'odeur de la cigarette) ou distants (une personne associée au tabagisme) (Conklin, 2006). Comparativement aux hommes, les femmes semblent moins influencées par la nicotine elle-même que par les stimulis à proximité (Perkins et al, 2006). Ces différences vont peut-être nous permettre d'améliorer notre compréhension étiologique de l'usage de la nicotine et aider à la mise sur pied de traitements propres aux genres.…”
Section: Stimulantsunclassified
“…Expectancy can also refer to whether participants expect an active or inactive substance in a study. This variable is more precisely termed "stimulus expectancy" (Kirsch, 1999;Perkins et al, 2004). Stimulus expectancy can be manipulated through instructional sets, in which some participants are told to expect an active drug and others are told to expect an inactive control.…”
mentioning
confidence: 99%